Breast cancer risk factors - Kamińska, Marzena; Ciszewski, Tomasz; Łopacka-Szatan, Karolina; Miotła, Paweł; Starosławska, Elżbieta (Menopause Review/Przegląd Menopauzalny, 2015)
Breast cancer is the most frequently diagnosed neoplastic disease in women around menopause often leading to a significant reduction of these women’s ability to function normally in everyday life. The increased breast cancer incidence observed in epidemiological studies in a group of women actively participating in social and professional life implicates the necessity of conducting multidirectional studies in order to identify risk factors associated with the occurrence of this type of neoplasm. Taking the possibility of influencing the neoplastic transformation process in individuals as a criterion, all the risk factors initiating the process can be divided into two groups. The first group would include inherent factors such as age, sex, race, genetic makeup promoting familial occurrence of the neoplastic disease or the occurrence of benign proliferative lesions of the mammary gland. They all constitute independent parameters and do not undergo simple modification in the course of an individual’s life. The second group would include extrinsic factors conditioned by lifestyle, diet or long-term medical intervention such as using oral hormonal contraceptives or hormonal replacement therapy and their influence on the neoplastic process may be modified to a certain degree. Identification of modifiable factors may contribute to development of prevention strategies decreasing breast cancer incidence.